2013
DOI: 10.2147/jpr.s40158
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study to investigate the use of a bupivacaine-collagen implant (XaraColl) for postoperative analgesia following laparoscopic surgery

Abstract: BackgroundXaraColl, a collagen-based implant that delivers bupivacaine to sites of surgical trauma, has been shown to reduce postoperative pain and use of opioid analgesia in patients undergoing open surgery. We therefore designed and conducted a preliminary feasibility study to investigate its application and ease of use for laparoscopic surgery.MethodsWe implanted four XaraColl implants each containing 50 mg of bupivacaine hydrochloride (200 mg total dose) in ten men undergoing laparoscopic inguinal or umbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recent examples have included a liposomal bupivacaine formulation (Exparel®) from Pacira Pharmaceuticals; [68-74] bupivacaine formulation (Posimir®) described as an esterified sugar derivative on the Durect website;[116] a poly(ortho ester) formulation of bupivacaine and the anti-inflammatory drug meloxicam (HTX-011) from Heron Therapeutics;[117,118] and a collagen-based implantable bupivacaine release system (XaraColl ®) from Innocoll. [119-121] A review focused on the engineering of sustained release systems is not the best place to review the comparative merits of commercial products, their tribulations with regulatory bodies, or to review clinical trials. Moreover, the abovementioned difficulties in comparing formulations in animals can be true of human trials as well.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…Recent examples have included a liposomal bupivacaine formulation (Exparel®) from Pacira Pharmaceuticals; [68-74] bupivacaine formulation (Posimir®) described as an esterified sugar derivative on the Durect website;[116] a poly(ortho ester) formulation of bupivacaine and the anti-inflammatory drug meloxicam (HTX-011) from Heron Therapeutics;[117,118] and a collagen-based implantable bupivacaine release system (XaraColl ®) from Innocoll. [119-121] A review focused on the engineering of sustained release systems is not the best place to review the comparative merits of commercial products, their tribulations with regulatory bodies, or to review clinical trials. Moreover, the abovementioned difficulties in comparing formulations in animals can be true of human trials as well.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…Randomized controlled trials performed in women undergoing open gynecological surgery3 and in men undergoing hernioplasty4 have concluded that XaraColl is effective in reducing patient use of opioid analgesia and/or their pain intensity for up to 3 or 4 days postoperatively. The product also offers great versatility and is already proven suitable for use in laparoscopic surgery 5. The primary objective of this study was to characterize XaraColl’s pharmacokinetic profile and elucidate its mechanism of drug release in vivo.…”
Section: Introductionmentioning
confidence: 99%